Everything You Always Wanted to Know About Data Citations* (*But Were Afraid to Ask) - Jeliazkova, Nina; Exner, Thomas; Willighagen, Egon (Zenodo, 2020)
Presentation at the joined RiskGONE, NanoSolveIT, NanoCommons workshop in Reykjavik/Iceland on January 6th, 2020.